PENGEMBANGAN MEDIA PEMBELAJARAN SCRAPBOOK MATERI KARANGAN DESKRIPSI MATA PELAJARAN BAHASA INDONESIA KELAS III SEKOLAH DASAR - Tiara Kusnia Dewi; Rina Yuliana (Universitas Muria Kudus, 2018)
This study aims to find out how to develop scrapbook learning media for the material essay description on the subjects of Indonesian in grade III primary school and to determine the feasibility of scrapbook learning media for the material essay description on the Indonesian language in grade III developed elementary school received a judgment worthy of experts. This research was conducted in SDN Banjar Agung 4 with the subjects of class III-A students of 28 students with the details of 17 students on a limited trial. The type of research used refers to the development model Thiagarajan, Semmel, and Semmel. This model consists of 3 stages namely, defining (define), planning (design), development stage (develop). The instruments used are questionnaires for media validation by expert lecturers as well as teacher and student response questionnaire. Based on data analysis, it can be concluded that the quality of scrapbook media developed is included in very decent category with 96.11% percentage from 2 material experts, very decent category with 85% percentage from 2 media experts, and 94% from 2 linguists. Student response to media scrapbook on trial with 17 respondents equal to 89,83% with very good category.